THE DEVELOPMENT OF LEARNING MODULE WITH A SOCIO-CULTURAL CONTENT FOR CRITICAL THINKING - Amalia Sholihati; Wuryandani Wuri (Borys Grinchenko Kyiv Metropolitan University, 2019)
This research has aims: develop learning module generates critical thinking to the charge sociocultural holy, and determine the effectiveness of the learning modules think critically charged sociocultural holy developed in The Class III Elementary school. This research use method research and development (RnD) by Gall, Gall, & Borg (2003). Research participant total 61 students elementary school, male= 28 & female 33, in 10-12 years old (M=11). The data analysis technique used to assess the success of the learning module is to use a questionnaire. The results of the analysis of data from the development of a slightly critical Learning Module with sacred sociocultural content in class III elementary school are appropriate to use. The results of this research and development were declared feasible by experts with an average value of 3.6 for the results of the validation of the material experts and 3.2 for the results of the validation of the media experts, from the data obtained good data. Learning Module developed demonstrates the effectiveness of the data.